Literature Review Analysis of the Effect of Leadership, Organizational Culture, and Work Environment on Employee Productivity - Yandi, Andri (Green Publisher, 2022)
The success of an organization to achieve its goals and objectives as well as the ability to face challenges and obstacles, both internal and external is determined by good human resources. Therefore the management of human resources is very important in an organization. Work productivity is one form of the ability of human resources in production that produces an output. The higher the level of work productivity in an organization is certainly very influential in achieving the goals of an organization. This article aims to explain the variables or factors that affect employee productivity in an organization. There are 3 variables that will be discussed in this article, namely leadership, organizational culture, and work environment. These three variables will be discussed from several points of view. Be it leadership, organizational culture, and work environment have an important influence in increasing employee productivity.